Otolith Marking With Strontium for Stock Assessment in Coilia nasus - Liu, Ming-Zhi; Jiang, Ri-jin; Zhang, Hui; Yang, Fan; Li, Xia-Fang; Feng, Guang-Peng; Yin, Rui; Chen, Feng (Frontiers in Marine Science, 2022)
This study reports that a 12 mg/L concentration of strontium and a treatment duration of 4 days constitute the ideal conditions for strontium marking of otoliths in C. nasus. The authors also suggest that post-treatment, the fish should be cultured in natural water in order to avoid the potential adverse effects of strontium consumption in humans. These recommendations are of benefit to the fishing industry, as this can help recover the loss of C. nasus resources. Moreover, the techniques described here can be explored further for stock assessment and enhancement of other economically important fish species.